Financial Control over the Activities of State-Owned Corporations in the Russian Federation - ASHTAEVA, Saglar S.; RUBEKO, Georgiy L.; LIDZHEEVA, Kermen V.; IVANENKO, Anna V.; OSADCHENKO, Elvira O. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
State-owned corporations in Russia act today as independent subjects of legal relations, including the financial component. Taking into account the fact that the state-owned corporations were established at the expense of budgetary (public) funds at quite significant financial investments of the state in these structures, certain risks were associated with effective management of these assets. In this regard, the state deliberately and consistently provides effective legal regulation of financial control over corporate activities. Property, contributed by the Russian Federation, including financial means, served as the basis for economic development of corporations. The ambiguous situation with the transfer of all rights on federal property and the lack of necessary control over this property was widely criticized. In March 2008, the Expert Council of the Committee on Industrial Policy of the Russian Federation Council (Report of the Expert Council, 2007) concluded that the functions carried out by state-owned corporations can and should be performed either by federal executive bodies, or commercial organizations, whose capital partly belongs to the state.
Keywords: state-owned corporations, financial control, budgetary funds, state financial investments, Industrial policy